PERANCANGAN APLIKASI SIMBA BERBASIS WEB UNTUK MENINGKATKAN MANAJEMEN BARANG PADA SUB BAGIAN PERENCANAAN DI DINAS LINGKUNGAN HIDUP KOTA TANGERANG SELATAN - Ghali Syarafi; Rengga Herdiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The many technologies that are currently developing make it easy for any work to be done, one of which is a website-based application where every company or office has a website. Based on the description above, the author tries to create a stock management website design that aims to make it easier to manage consumables that are often used in offices. The use of the website is expected to improve the management of goods in an office, Dinas Lingkungan Hidup Kota Tangerang Selatan. This goods management system was developed using the waterfall development method, with the PHP programming language and the database used is MySQL. It is hoped that this goods management system can improve the management of goods in an office.